The Effect of Dividend Policy and Debt Policy on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Devi Lestari Pramita Putri; Runik Puji Rahayu; Rani Nur Fitrianti (ULTIMA Management, 2026)
A company's choice to either distribute profits to shareholders or save them for use in future investments is reflected in its dividend policy. A company's debt policy, on the other hand, reveals how it plans to obtain outside money for its needs. Through financial stability and investor views, both policies have the potential to affect a company's value. The purpose of this study is to examine how the value of manufacturing firms in the products industry subsector listed on the Indonesia Stock Exchange (IDX) for the years 2022–2023 is impacted by dividend and debt policies. Out of the 40 companies in the population, 30 were chosen for the study sample using purposive sampling procedures. Multiple linear regression, hypothesis testing, and traditional assumption tests were used to analyze the data. The findings indicate that whereas debt policy, as measured by the debt to equity ratio, has no discernible impact on firm value, dividend policy, as measured by dividend yield, has a positive and significant impact. The company value, as measured by Tobin's Q, is significantly impacted by both independent factors at the same time. These results demonstrate that raising dividends can boost a company's worth, but maintaining financial performance and investor faith in the company's future depends on prudent debt management